Synthesis and Characterization of Novel Nitride Phosphors Ca5Si2N6: Eu2+/Ce3+ - Huang, Jinzhao; Jiang, Tao; Yao, Nannan; Li, Honglin; Xu, Xijin (Asian Journal of Chemistry, 2015)
The novel nitride phosphor Ca5Si2N6: Eu2+/Ce3+ were successfully synthesized at 1450 °C via a solid-state reaction method under a nitrogen atmosphere. The photoluminescence of Ca5Si2N6: Eu2+/Ce3+ shows that the phosphors have the main emission peak at 609 and 470 nm, respectively. The phosphor Ca5Si2N6: Eu2+ can be excited in the range from 350 to 480 nm, which makes it the attractive candidate phosphors for the application in phosphor-converted light-emitting diodes as red phosphors. The Ca5Si2N6:Ce3+ can be effectively excited by near ultraviolet. Moreover, the effect of doping concentration on the luminescence property is investigated.